Correction of velopharyngeal insufficiency secondary to palatal gunshot wound: case presentation and review of the literature - Martínez-Wagner, Rogelio; Cardenas-Cruz, Cristopher; Ortiz-Monasterio, Iván; Vargas, Edgar; Cabrera, María M.; Ysunza, Pablo A.; Pamplona, M. Del Carmen; Campos-Lopez, Diana E. (International Surgery Journal, 2022)
Reconstruction of midfacial traumatic defects secondary to a gunshot wound (GSW) is one of the most challenging head surgeries. The high impact on the functional and aesthetic quality of life, and the small margin of error to achieve a successful outcome are significant hurdles in the surgical treatment of these cases. Here we report a 33-years old patient who suffered a GSW with an entrance wound penetrating between the soft and hard palate and an exit wound on the right malar region. A description of the case and a systematic review of the literature were conducted. The treatment depends on the type of weapon used, deforming characteristics of the bullet, kinetic energy, place of impact, and general conditions of the patient. GSW generate a particular injury due to their special trauma kinematics. In this case, our patient required extensive reconstructive surgery with interposition of costal cartilage to recover velopharyngeal structure and function, patients treated with this surgical strategy develop fewer complications such as infection, shrinkage, scarring. As demonstrated by this case report, the result can be satisfactory. In order to provide the most beneficial results for the patient, surgical techniques are evolving continuously, improving both structure and function, and increasing the quality of life of the patients. Free flaps are preferred because of the good results reported. Patients treated with this surgical strategy develop fewer complications such as infection, shrinkage, scarring. As demonstrated by this case report, the result can be satisfactory.